2020
DOI: 10.3889/oamjms.2020.4866
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Pain and Work-related Risk Factors among Waste Collectors in Hanoi, Vietnam: A Cross-sectional Study

Abstract: BACKGROUND: Musculoskeletal disorders (MSDs) are prevalent among waste collectors (WCs) in developing countries. AIM: This study aimed to investigate the prevalence of MSDs and the factors associated with the risk of persistent musculoskeletal pain among WCs in Hanoi, Vietnam. METHODS: A cross-sectional survey was utilized to study 468 WCs in 2017. The Örebro Musculoskeletal Pain Questionnaire and a questionnaire on demographic and work conditions were used to collect data. Descriptive and multivar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
2
2
0
1
Order By: Relevance
“…These findings corroborate the results of previous studies. These findings corroborate with the results of studies conducted in Nigeria [25], India [26], Vietnam [27], Thailand [28], Korea [7], and Iran [29] with the observed prevalence of 78.2%, 72%, 74.4%, 88%, 69.4%, and 93% respectively. In contrast, a lower prevalence was observed in the studies conducted in Malaysia (54.5%), Egypt (60.8%), Brazil (60%), Australia (58.1%), Mekelle, Ethiopia (53.28%), and India (Chandigarh 56.8, Himachal Pradesh 58.9 [30][31][32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings corroborate the results of previous studies. These findings corroborate with the results of studies conducted in Nigeria [25], India [26], Vietnam [27], Thailand [28], Korea [7], and Iran [29] with the observed prevalence of 78.2%, 72%, 74.4%, 88%, 69.4%, and 93% respectively. In contrast, a lower prevalence was observed in the studies conducted in Malaysia (54.5%), Egypt (60.8%), Brazil (60%), Australia (58.1%), Mekelle, Ethiopia (53.28%), and India (Chandigarh 56.8, Himachal Pradesh 58.9 [30][31][32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 91%
“…The higher illiteracy rate (41%) amongst the street sweepers observed in this study is similar to those observed in most of the countries [ 25 , 27 , 30 , 31 ]. Further, there are some significant predictor variables identified in the logistic model, such as higher age, being overweight/obese, not-satisfied with the job, and cleaning long distances in a day.…”
Section: Discussionsupporting
confidence: 88%
“…De forma general, el riesgo predomina en los hombros, cuello, brazos, piernas, tronco y muñecas. Un estudio realizado a recolectores en Vietnam muestra que la espalda baja resultó ser el sitio más afectado, seguido por el cuello y hombros (Nguyen et al, 2020). Otra investigación, identifica que el riesgo más significativo se encuentra en los brazos con un 80.6 %, muñecas/manos con un 74.2 %, y espalda con un 67.7 % (Tuesca-Armijos, 2020).…”
Section: Discussionunclassified
“…Interestingly, the study found no difference in prevalence between male and female respondents. According to a study by Nguyen et al, 28 lower back pain was the most frequently reported, followed by neck and shoulder pain. The study also found that age was significantly associated with persistent musculoskeletal pain and that female workers had a higher risk of persistent disorders.…”
Section: Body Painmentioning
confidence: 98%